Economic Well-Being among Men 55-64 Without Earnings: A Six Country Comparison - Martin Rein; Lee Rainwater (Luxembourg Income Study (LIS), 1990)
This paper analyzes how the economic penalty for labor withdrawal and the cushions created by society affect the persistent trend toward early retirement of men in their late fifties and early sixties. Microdata for six LIS countries is used to determine why this early exit took place in the past decade and whether the trend will continue.
Keywords: 330